Optimization and Development of Albumin–Biopolymer Bioconjugates with Solubility-Improving Properties - Zsófia Edit Pápay; Sabrina Magramane; Márton Király; Petra Szalkai; Krisztina Ludányi; Péter Horváth; István Antal (Biomedicines, 2021)
Bioconjugation is an emerging field in the food and pharmaceutical industry. Due to its biocompatibility and high ligand binding capacity, albumin is widely used in modern drug delivery systems. However, the protein is sensitive to environmental stresses; albumin conjugates, on the other hand, have improved functional properties. Biopolymers are gaining interest due to their biodegradability and safety, compared to synthetic polymers. In this study, albumin–biopolymer bioconjugates were prepared by nonenzymatic Maillard reaction at 60 °C and 80% relative humidity. This nonenzymatic conjugation takes place between reducing sugars and available amino groups of a protein in certain conditions. The optimal molar ratio and time for the conjugation were studied by several investigation methods, including circular dichroism and fluorescence spectroscopy, sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE), and determination of available amino groups with ortho-phthaldialdehyde (OPA) assay. All of the measurements provided evidence for the covalent bonding of albumin and biopolymers, resulting in bioconjugates. Based on the results, a higher molar ratio and longer time are necessary to complete the reaction with the available amino groups. However, the optimal parameters are specific to each given biopolymer. The rheological behavior of the conjugates is characteristic of the initial biopolymer, which can be useful in drug development. Moreover, both the physical characteristics of albumin and the solubility-improving capacity were enhanced. Therefore, the potential use of albumin–biopolymer bioconjugates in the pharmaceutical industry could be considered.